Predeployed aortic extension cuff (kilt) in EVAR with hostile neck anatomy using Endurant II system: preliminary results - Szaniewski, Krzysztof; Biernacka, Magdalena; Walas, Ryszard L.; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction : Various modifications of standard endovascular aortic aneurysm repair (EVAR) have been developed to solve the problem of difficult neck anatomy. Aim: The authors propose the implantation of a predeployed extension cuff (kilt) using on-shelf Endurant II elements. In a vast majority of cases, the proposed method provides a solution for the hostile neck problem using standard Endurant II elements available in all centers performing subrenal EVAR procedures. Material and methods: The early outcomes of kilt implantation were evaluated in 11 patients (three with ruptured abdominal aortic aneurysms, one symptomatic) in 2 vascular centers in Silesia (Poland). All patients presented with hostile neck anatomy defined as neck length 28 mm, angulation > 60°, mural thrombus or calcium > 2 mm in thickness or > 180° circumference. Results: No intraoperative type I endoleak or device migration was observed. Two perioperative deaths occurred in patients in a severe condition with ruptured aneurysms. One case of type III endoleak was managed by the implantation of an additional iliac extension with complete endoleak sealing. Conclusions : The proposed method seems to be effective in early endoleak prevention in patients with hostile neck anatomy undergoing EVAR procedures; however, studies with long-term follow-up are needed.